Implementasi Problem Based Learning dalam Mengoptimalkan Pembelajaran di Sekolah Luar Biasa Putera Asih Kediri - Sufirmansyah Sufirmansyah; Laundria Nanda Prameswati (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
Abstract: This article aims to reveal the media and learning strategies at SekolahLuar Biasa (SLB) Putera Asih Kediri. Education is something important for everyIndonesian citizen. It does not distinguish between gender, ethnicity, race, culture,religion, even for children with special needs (Anak Berkebutuhan Khusus/ABK).However, the media and learning strategies used by the teacher in an extraordinaryschool (SLB) are certainly different from the teachers in public schools. This articlewas written according to a qualitative research that used a case study approach toreveal the implementation of PBL in SLB Putera Asih Kediri. This article concludethat every school needs creative teachers to use media and learning strategi es. Forthis reason, it is expected that each young generation can utilize media and learningstrategies that are appropriate to the needs of the students. PBL is very relevantwith the needs of ABK in SLB because it can be combined with the teacheroriented study. PBL can be used as an alternative learning strategy to increase theunderstanding of ABK, so they can solve their daily problems